THE RELATIONSHIP OF MOBILIZATION WITH THE EVENT OF DECUBITUS IN THE INTENSIVE CARE UNIT (ICU) ROOM PATIENTS OF THE LINGGAJATI REGIONAL GENERAL HOSPITAL KUNINGAN REGENCY IN 2015 - Kasmad -; Amirul Kadafi; Dewi Erna Marisa (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2022)
Decubitus is defined as an injury due to the patient's position which has not changed for more than 6 hours. Decubitus is a localized tissue that tends to occur when soft tissue is compressed between the bony prominence and the external surface for a long period of time. This study aims to identify the relationship between mobilization and the incidence of pressure sores in the ICU room at Linggajati Regional General Hospital. The design of this study used a descriptive analytic study with an accidental sampling technique of 11 patients. The instruments used are in the form of questionnaires and checklists with univariate and bivariate analysis with chi-square. The chi-square analysis test obtained a p-value of 0.01 (α : 0.05), P< so that Ho was rejected and Ha was accepted, which means that there is a relationship between mobilization and the incidence of pressure sores at Linggajati Regional General Hospital Kuningan Regency. In 11 respondents studied, there were 5 people (45.4%) who had less mobilization, 4 people (36.4%) had sufficient mobilization and 2 people (18.2%) had good mobilization. Then the results of the respondent's decubitus assessment there were 5 people (45.4%) who had pressure sores and 6 people (54.5%) did not. There is a relationship between mobilization and the incidence of pressure sores in patients in the Intensive Care Unit (ICU) Linggajati Regional General Hospital, Kuningan Regency. Suggestions for nursing staff to set standard operating procedures for treating patients in the ICU, especially patients with severe disease and limited mobility. It is recommended to conduct further research related to all the factors that influence the occurrence of pressure sores in ICU patients, especially implementing nursing care and setting standard operating procedures.